High activity electrocatalysts from metal-organic framework-carbon nanotube templates for the oxygen reduction reaction - Ge, L.; Yang, Y.; Wang, L.; Zhou, W.; De Marco, Roland; Chen, Z.; Zou, J.; Zhu, Z. (Elsevier Ltd, 2015)
Developing economical and commercially available materials to replace precious and nondurable platinum based catalysts is a very important issue in contemporary fuel cell technology. Nanostructured carbon materials have the potential to reduce the costs, improve the fuel tolerance and scalability; however, they are limited presently by their relatively low catalytic activity. Herein, we have synthesized a new electrocatalyst for the oxygen reduction reaction derived from in situ growth of metal-organic frameworks on carbon nanotubes, followed by pyrolysis. The most efficient catalyst yielded comparable catalytic activity than commercial platinum-based catalysts and a low Tafel slope of 49 mV dec-1. This excellent performance is attributable to the formation of 3D structured porous and N doped carbon/carbon nanotubular composites. High surface area and continuous catalytic layer on graphitic carbon boosts the active sites and reactivity during electrolysis.